Kontribusi Pola Asuh Orang Tua, Teman Sebaya, Iklim Sekolah, dan Minat Belajar Terhadap Hasil Belajar PPKn Siswa Kelas XI SMK Negeri 1 Denpasar - Ni Kadek Marini; Kadek Rihendra Dantes; Basilius Redan Werang (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to analyze the contribution of parenting, peers, school climate, and student learning interest to the learning outcomes of Pancasila and Civic Education (PPKn) of grade XI students at SMK Negeri 1 Denpasar. The research method used was quantitative involving 152 respondents of class XI students. Data were collected through questionnaires and documentation, then analyzed using regression statistical techniques. The results showed that parenting, interaction with peers, school climate, and interest in learning together contributed significantly to PPKn learning outcomes by 66.70%. Positive parenting, good social interaction with peers, a conducive school climate, and high interest in learning have a positive influence on the achievement of student PPKn learning outcomes. The implications of this study are the need for further attention to the role of parents in shaping parenting, the development of healthy social interactions among students, improving the school climate, and efforts to stimulate student interest in learning. These findings can be the basis for schools, parents, and policy makers to design programs that support the improvement of PPKn learning outcomes at SMK Negeri 1 Denpasar. In addition, this research can also contribute to a broader understanding of the factors that influence learning outcomes at the Vocational High School level.